Guidelines for Effective Professional and Academic Writing - Ralph G. Easterly; Brian E. Myers; Alison E. Lutz; Nick T. Place (EDIS, 2010)
Revised! AEC382, a 3-page fact sheet by R.G. Easterly III, B.E. Myers, A.E. Lutz, and N.T. Place, provides a few tips to keep in mind while composing professional documents. Published by the UF Department of Agricultural Education and Communication, January 2010.